Unripe grapes: an overview of the composition, traditional and innovative applications, and extraction methods of a promising waste of viticulture. (3rd October 2021) - Fia, G.; Bucalossi, G.; Proserpio, C.; Vincenzi, S.
Abstract: Unripe grapes (UGs) are a waste product of grapevine cultivation and an emerging source of several compounds, such as organic acids, phenolic compounds, vitamins and mineral salts, of great economic importance to the pharmaceutical, cosmetic and food industries. Traditionally, products made from UGs, such as verjuice and sour grape sauces, have been used as seasoning or acidifying agents. The health effects of grape compounds are described as anti‐inflammatory, cardioprotective, anticancer and antidiabetic, as often demonstrated by both in vitro and in vivo studies. Recently, UGs have received renewed attention because of the innovative potential applications of their extracts in food and beverages for purposes of preservation and enrichment with healthy compounds, or for direct use in the human diet. The aim of this article is to review the composition and properties of UG products and their traditional and innovative application in food and beverages.